Penguatan Solidaritas Remaja Melalui Kegiatan Karawitan di Desa Banaran pulung ponorogo - Agystina Dwi Kartika Putri; Kayyis Fithri Ajhuri (Social Science Academic, 2025)
This research explores the role of traditional Javanese music, or karawitan, as a medium for strengthening the social solidarity of adolescents in Banaran Village, Pulung District, Ponorogo. Using a qualitative case study approach, the study involved participant observation, in-depth interviews, and documentation analysis with active youth participants in karawitan activities. The findings reveal that karawitan serves as an effective platform to instill values such as cooperation, discipline, mutual respect, and collective responsibility. Through the dynamics of group practice and performance, adolescents develop social bonds, enhance cultural awareness, and cultivate a stronger sense of belonging. Despite some challenges, such as peer pressure and time management between school and practice, karawitan proves to be a valuable cultural and educational tool for character development among youth.